Predicting the dyadic coping through self-esteem among infertile couples undergoing in vitro fertilization and embryo transfer: An actor-partner interdependence model - Zhang, Lihong; Gu, Wei; Jing, Xiaoyu; Zhi, Shihan; Zhou, Nan; Zhang, Lu; Wang, Wenru; Jiang, Ying (Frontiers in Psychology, 2023)
Background The population of infertile couples receiving in vitro fertilization and embryo transfer in China is increasing gradually. The association of self-esteem and dyadic coping of infertile couples undergoing in vitro fertilization and embryo transfer has not been reported. This investigation aimed to examine the predictive effect of self-esteem of infertile couples undergoing in vitro fertilization and embryo transfer on coping strategies at the dyadic level. Methods A cross-sectional study involving 283 infertile couples was conducted at the Reproductive Center of Northwest Women and Children’s Hospital in China. Participants were asked to complete two self-administered questionnaires, to assess self-esteem (Rosenberg Self-Esteem Scale) and dyadic coping (Dyadic Coping Inventory). Paired t-test and Pearson correlation were used to analyze the difference and correlation of variables between wife and husband. The actor-partner interdependence model was used to test the predictive effect of each individual’s self-esteem on their own and their partners’ dyadic coping. Results Infertile couples’ self-esteem and dyadic coping are in the medium range. The self-esteem of wives and husbands can fully predict their own dyadic coping. Meanwhile, the husband’s self-esteem can predict the wife’s stress communication (β = 0.135, p = 0.025), support dyadic coping (β = 0.142, p = 0.019), and negative dyadic coping (β = 0.133, p = 0.024), and the wife’s perceived partners’ supportive dyadic coping (β = 0.147, p = 0.014) and negative dyadic coping (β = 0.144, p = 0.016). Similarly, the wife’s self-esteem can predict the husband’s supportive dyadic coping (β = 0.195, p < 0.001), and the husband’s perceived partners’ stress communication (β = 0.184, p = 0.003) and supportive dyadic coping (β = 0.180, p = 0.002). Conclusion The actor-partner analyses revealed insight into how infertile couples undergoing in vitro fertilization and embryo transfer interact and highlighted the importance of self-esteem in dyadic coping styles. Future psychological interventions can enhance self-esteem as an effective way to improve dyadic coping of infertile couples.